2020
DOI: 10.22541/au.159007761.13746208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac Involvement in a Pediatric Patient with COVID-19: Looking Beyond the Nonspecific Global Cardiac Injury

Abstract: We report a case of a 17-year-old healthy male presenting with multisystem hyperinflammatory shock temporally associated with COVID-19. Cardiac involvement was suspected based on evidence of significant cardiac injury (elevated cardiac biomarkers, electrocardiographic and echocardiographic abnormalities). Cardiac magnetic resonance imaging was performed demonstrating global biventricular systolic dysfunction, as well as a small area of T2 hyperintensity and mid wall late gadolinium enhancement. This case discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Case reports and small series have described cardiogenic shock, myocarditis, pericarditis, and arrhythmias. 67–70 Arrhythmias have included ventricular tachycardia and atrial tachycardia, as well as first-degree atrioventricular block. 15,71 Although arrhythmias are generally nonsustained and self-resolve without need for treatment, prophylactic antiarrhythmics have been administered in some cases, 15 and death caused by recurrent ventricular tachycardia in an adolescent with hypertrophic cardiomyopathy has been described.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Case reports and small series have described cardiogenic shock, myocarditis, pericarditis, and arrhythmias. 67–70 Arrhythmias have included ventricular tachycardia and atrial tachycardia, as well as first-degree atrioventricular block. 15,71 Although arrhythmias are generally nonsustained and self-resolve without need for treatment, prophylactic antiarrhythmics have been administered in some cases, 15 and death caused by recurrent ventricular tachycardia in an adolescent with hypertrophic cardiomyopathy has been described.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In a young patient with shock state due to COVID-19, diminished LVEF of 40% and regional hypokinesia were confirmed by CMRI demonstrating global biventricular systolic dysfunction, as well as a small area of T2 hyperintensity and mid-wall LGE [12]. In another study investigating athletes with a history of COVID-19, it was reported that 9% had LGE in CMRI.…”
Section: Discussionmentioning
confidence: 91%
“…This distribution pattern is typically seen during or after myocarditis (20). In COVID-19 patients with MISC or isolated heart involvement, an identical MRI image with this myocarditis type is seen in all degrees of myocardial involvement (21). Edema in the myocardium can be observed in myocarditis up to 6 months after the disease, depending on the severity of myocardial involvement (22).…”
Section: Late Gadolinium Enhancement Persists In All Patients After S...mentioning
confidence: 99%